Life After Graduation : A Systematic Literature Review of Life Design Career Counseling for High School Students - Salma Nurul Baidho; Sinta Saraswati (Jurnal Studi Guru dan Pembelajaran, 2025)
The challenges of globalization, rapid technological advancement, and dynamic job markets have increased the urgency of career planning among high school students. This study aims to systematically review the effectiveness, conceptual approaches, and procedural techniques of Life Design Career Counseling (LDCC) in addressing students' career dilemmas, particularly those related to post-secondary education choices. Using a systematic literature review method based on PRISMA-P standards, A total of 10 primary studies published within the last 10 years were selected based on specific inclusion criteria: relevance to high school students (or equivalent), focus on career development using the LDCC model, and publication within the 2015–2025 period. Studies unrelated to upper-secondary level populations or lacking primary data were excluded. Literature was gathered from Google Scholar, SINTA Ristekbrin, and Elsevier. The findings indicate that LDCC effectively enhances students' career adaptability, vocational certainty, self-efficacy, optimism, and reflective capacity. Grounded in Career Construction Theory (CCT), LDCC utilizes narrative-based approaches, such as the Career Construction Interview (CCI), to help students make sense of their life stories and align them with meaningful career goals. The implementation of LDCC varies across individual, group, and online settings, typically delivered over 3 to 8 sessions. Techniques like storytelling, visual-symbolic tools, and structured interviews were found to be adaptable for diverse student populations, including those with special needs and in resource-constrained contexts. This review concludes that LDCC offers a holistic and personalized intervention framework that supports students' self-exploration and future career planning. The study highlights the practical implications for school counselors to adopt LDCC as a proactive career intervention method tailored to students' developmental and contextual needs.